Improving Studentsâ Reading Comprehension by using Semantic Mapping in Pre-reading: A Classroom Action Research to the Tenth Grade Students of a Senior High School in Mempawah - Avrianti, Neneng (IKIP-PGRI Pontianak, 2015)
This research focuses on improving reading comprehension by using semantic mapping in pre-reading of the tenth grade students of one senior high school in Mempawah. There are some problems appeared in classroom while reading learning. The students have difficulties in reading comprehension. For that reason, the researcher conducted Classroom Action Research. The research was conducted in two cycles. It is followed by evaluation of a test. The finding showed that studentsâ reading comprehension of the tenth grade has improved. Then, the studentsâ responses to learning were positive. Their participation in cycle II has improved from cycle I and the teaching learning process was good. Semantic mapping is a good technique, which can be applied by the teacher in the classroom to improve the studentsâ reading comprehension.